Diaryl Pyrazole-4-carbaldehyde Benzoylhydrazones Metal Complexes: Synthesis and Their Antibacterial and Antioxidant Screening - Nasrullah, Muhammad; Ain Khan, Misbahul; Naeem Khan, Muhammad; G. Humphrey, Mark; Hassan Nasim, Faizul; Chaudhry, Faryal; Ghazal Abidi, Moeena; Farooq, Umar; Ali Munawar, Munawar (Asian Journal of Chemistry, 2012)
Various heterocyclic ligands [1,3-diarylpyrazole-4-carbaldehyde benzoyl-hydrazones] and their metal complexes with Cu2+, Ni2+, Co2+, Pb2+, Zn2+ and Fe2+ have been synthesized, characterized and screened for their antibacterial and antioxidant activities. The synthesized compounds were characterized through elemental analysis and spectroscopic techniques (FTIR, 1H NMR and Mass).